Twelve new species of Cyrtodactylus Gray (Squamata: Gekkonidae) from isolated limestone habitats in east-central and southern Myanmar demonstrate high localized diversity and unprecedented microendemism. Issue 4 (21st October 2017) - Grismer, L Lee; Wood, Perry L; Thura, Myint Kyaw; Zin, Thaw; Quah, Evan S H; Murdoch, Matthew L; Grismer, Marta S; Lin, Aung; Kyaw, Htet; Lwin, Ngwe
Abstract: Twelve new karst-adapted species of the gekkonid genus Cyrtodactylus Gray are described from the Shan Hills and Salween River Basin of Myanmar. Three species occur in rocky habitats along karst ridges and nine species are microendemics restricted to isolated karst caves and towers. This high, localized diversity underscores the archipelago-like nature and microendemism associated with karst habitat-islands. Eleven of the 12 new species are not related to other Indo-Burmese species and form four monophyletic species groups nested within a larger Indo-Chinese clade of Southeast Asian species. Phylogenetic relationships and distributions indicate Cyrtodactylus originated in the Himalayan uplands and dispersed westward through Myanmar with subsequent invasions back into eastern and southern Myanmar. These new species highlight the understudied nature of karst biodiversity in general and karst herpetology in particular. Extensive karst ecosystems throughout the massive Shan Plateau of eastern Myanmar remain largely unexplored and are likely to harbour tens—if not hundreds—of undiscovered species. The unique and complex structure of understudied limestone ecosystems throughout Southeast Asia are habitats in which amphibians and reptiles have specialized, speciated and become endemic. In an age of biodiversity crisis, managing and conserving these ecosystems throughout Southeast Asia should be given greater priority. A key to the species of Cyrtodactylus of Myanmar is provided.